(untitled) (Jurnal Simki Economic, 2025)
This study aims to analyze the effect of job satisfaction on employee performance at PT. PLN Indonesia Power UBP Mahakam. The background of this study is that challenges are still found in achieving optimal performance even though the company has made efforts to improve job satisfaction. This study uses a quantitative approach with a total sampling method of 50 active employees. Data were collected through questionnaires, observations, documentation, and interviews, then analyzed using validity tests, reliability tests, classical assumption tests, simple linear regression, and t-tests with the help of SPSS version 25. The results of the study indicate that job satisfaction has a positive and significant effect on employee performance with a regression coefficient value of 0.758 and a significance value of 0.000 <0.005, which means that the higher the job satisfaction, the higher the employee performance. This finding emphasizes the importance of increasing job satisfaction as a strategy to support the achievement of organizational goals.